Exploring the impact of the dissertation in practice - Storey, Valerie Anne (Emerald Publishing Limited : Information Age Publishing, Inc, 2017)
Exploring the Impact of the Dissertation in Practice significantly contributes to our understanding of the design and impact of the Dissertation in Practice, the capstone of professional practice doctoral programs. Chapter authors are to be commended for sharing with the reader a broad and reflective view of their dissertation journey, and as a consequence give the reader insight into the nature of professional practice doctorate education in the early 21st century. Readers have the opportunity to hear firsthand how the dissertation is changing not only in format but also in the impact it makes in the field. Faculty and program graduates share accounts of their scholarly practice; the problems of practice that they have encountered and addressed in their professional practice; and their evolving role as change agents in their field of practice. In the process, they assist all faculty involved in designing and evaluating professional practice programs by identifying challenges and opportunities for construction of powerful end-of-program doctoral work. Individually and collectively chapter authors reflect on their experiences in creating practice-anchored and intellectually rigorous Dissertation in Practice.